Sistem Informasi Eksekutif Yayasan Madrasah Nasyril Islamiyah - Novri Hadinata (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
The Madrasah Nasyril Islamiyah Foundation (YAMNI) is an educational foundation that includes Madrasah Ibtidaiah, Madrasah Tsanawiyah and Madrasah Aliyah. The problem that occurs in YAMNI is that top management does not have a system that provides specific information such as student or student data, teacher or teacher data, infrastructure data to speed up decision making. From the problems found, it is determined that the purpose of this research is to build a website-based Executive Information System for YAMNI, which can be used as a provider of information needed by YAMNI leaders. The method that researchers use to create the system is the EIS Lifecycle method. That is, there are six phases: justification, design, business analysis, system design, system construction, and deployment and release phases. The results of this study are an Executive Information System that can manage student or student data, teacher or teacher data, infrastructure data from YAMNI and provide actual information to the head of the foundation to support decision making to quickly determine planning strategies and policies in various related fields. with the progress of YAMNI